Commuting preferences in Eastern Europe: case study in Town of Šiauliai - Jaržemskis, Andrius; Bazaras, Darius; Jaržemskienė, Ilona (Transport, 2023)
This article presents a study conducted in the Town of Šiauliai with a population of 100 thousand, located in the Republic of Lithuania, where the market economy has been operating for 32 years and which is a member of the European Union for 20 years. In the town, the share of commuting travels by car is significantly higher than by public transport. Since the availability of the public transport network is identified in scientific publications as one of the many criteria for choosing public transport, it was decided to conduct a study and check to what extent the availability of the public transport network determines the choice to travel by bus or car. The research hypothesizes that residents who live in neighbourhoods with worse access to bus routes and stops choose more cars than those who live in neighbourhoods with better access to public transport. The results of the study showed that residents choose to travel by bus or car regardless of the availability of the route network. It was found that the origin–destination pairs and relative proportions of those commuting to work match both those traveling by car and by bus. The results of this study may not necessarily be the same in Western European cities or towns. The main limitation of this article is that the trip matrices were compiled from population survey data, as statistical information on origin–destination pairs in Town of Šiauliai is not regularly collected.